2022
DOI: 10.1038/s41598-022-08528-y
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted connectivity in the olfactory bulb-entorhinal cortex-dorsal hippocampus circuit is associated with recognition memory deficit in Alzheimer’s disease model

Abstract: Neural synchrony in brain circuits is the mainstay of cognition, including memory processes. Alzheimer's disease (AD) is a progressive neurodegenerative disorder that disrupts neural synchrony in specific circuits, associated with memory dysfunction before a substantial neural loss. Recognition memory impairment is a prominent cognitive symptom in the early stages of AD. The entorhinal–hippocampal circuit is critically engaged in recognition memory and is known as one of the earliest circuits involved due to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…They are the earliest regions affected by AD, and the EC conveys spatial/contextual and object information to the hippocampus (van Strien et al, 2009;Knierim et al, 2014). Previous observations have revealed that coherent oscillatory activity in EC-Hip was correlated with object recognition memory performance (Salimi et al, 2022). Consistent with previous studies, the result in the present study has shown that EC and Hip are correlated with recognition memory performance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…They are the earliest regions affected by AD, and the EC conveys spatial/contextual and object information to the hippocampus (van Strien et al, 2009;Knierim et al, 2014). Previous observations have revealed that coherent oscillatory activity in EC-Hip was correlated with object recognition memory performance (Salimi et al, 2022). Consistent with previous studies, the result in the present study has shown that EC and Hip are correlated with recognition memory performance.…”
Section: Discussionsupporting
confidence: 91%
“…Compelling evidence demonstrated that altered recognition memory in both cognitive impairment patients and animals is potentially associated with changes in regional spontaneous activities and neural connectivity, including the hippocampalcortex network (Matura et al, 2014;De Marco et al, 2017;Tanimizu et al, 2018;Salimi et al, 2022). Previous studies found that EA not only increased the neuronal activity of the hippocampus in mild cognitive impairment (MCI) patients but also enhanced the functional connections between brain regions (Tan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together with a parallel body of literature indicating that early AD is characterized by smell loss 1-3 , amyloid deposition in the olfactory epithelium (OE), and olfactory sensory neuron (OSN) dysfunction 4, 5 , our study raises the possibility that viral infection of the OB/OT accelerates AD. Because sniff-induced beta and theta-coupled gamma oscillations generated in the OB are directionally coupled to the hippocampus 25-28 , smell loss would result in decreased hippocampal gamma oscillations that have been postulated to lead to neurodegeneration and cognitive decline 29-31 . These studies suggest that virus disruption of olfactory pathways can accelerate AD cognitive decline (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Because sniff-induced beta and theta-coupled gamma oscillations generated in the OB are directionally coupled to the hippocampus 1316 , smell loss would result in decreased hippocampal gamma oscillations that have been postulated to lead to neurodegeneration and cognitive decline. 1719 These studies suggest that alphaherpesvirus disruption of olfactory pathways can accelerate AD cognitive decline (Supplementary Figure 4).…”
mentioning
confidence: 95%
“…injection were carried out in accordance with our previous protocol. 28 Briefly, after anesthetizing, the animals were placed on the stereotaxic apparatus, and then the skull was exposed for finding the coordinates in the Paxinos atlas. Based on the reference points in the Paxinos atlas, we found the coordinates for OB (AP: 8.5 mm, ML: ± 1 mm, DV: − 1.5 mm), i.c.v.…”
Section: Surgery and Electrode Implantationmentioning
confidence: 99%